2019
DOI: 10.14309/01.ajg.0000596556.97196.f2
|View full text |Cite
|
Sign up to set email alerts
|

1756 Evolution of Esophageal Lichen Planus to Esophageal Leukoplakia

Abstract: INTRODUCTION: To describe a case of esophageal lichen planus which appeared to evolve to leukoplakia (aka epidermoid metaplasia). CASE DESCRIPTION/METHODS: A 70 yo female with a prior history of lichen planus, presented from another institution for ongoing care related to proximal esophageal stricturing. The patient had well-documented lichen planus involving the oral and vaginal mucosae and axillary areas. Dysphagia had been ongoing for greater than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ribolsi et al (9) reported a lower distal contractile integral (DCI) in patients with reflux esophagitis than that in patients with NERD. Another study indicated that the amount of reflux was associated with esophageal dysmotility in patients with systemic sclerosis (10). Esophageal motility dysfunction was reported to cause delayed esophageal emptying and prolonged esophageal exposure to acid and gastric juice, which ultimately lead to esophageal mucosal damages, inflammation, and reflux-related symptoms (11).…”
Section: Introductionmentioning
confidence: 99%
“…Ribolsi et al (9) reported a lower distal contractile integral (DCI) in patients with reflux esophagitis than that in patients with NERD. Another study indicated that the amount of reflux was associated with esophageal dysmotility in patients with systemic sclerosis (10). Esophageal motility dysfunction was reported to cause delayed esophageal emptying and prolonged esophageal exposure to acid and gastric juice, which ultimately lead to esophageal mucosal damages, inflammation, and reflux-related symptoms (11).…”
Section: Introductionmentioning
confidence: 99%